Morfogenesis Kalus Sorgum Pada Berbagai Media Secara In Vitro : Morphogenesis of Sorghum Callus on Various Media In Vitro - Suryaningsih, Dwie Retna (Journal of Applied Plant Technology, 2022)
Sorghum has great potential to be developed as a food source in Indonesia because it has many benefits. Sorghum has various potentials and uses, such as as a source of functional food, industrial raw materials and also animal feed. All parts of the sorghum plant can be utilized. Genetic transformation will be successful and beneficial if a plant regeneration system has been obtained in vitro culture. In its implementation, the selection of explants is an important first step to support the success of in vitro culture. Generally, the explants used for tissue culture are shoot tips, lateral shoots, and epicotyls. This study aims todetermine the morphogenesis of sorghum in vitro, from tissue culture. The analysis method in this study used 3 treatments, namely Murashige & Skoog (MS), Vacint & Went (VW) and Nagata & Takebe (NT) media with repeated 5 times. The method of analysis with data on the percentage of living callus and observing the morphogenesis of growing shoots and calluses. The result of this study is that the treatment of Murashige & Skoog (MS) media affects the morphogenesis of buds in the form of the number of perexplant shoots, the number of leaves, and the length of the shoots with the best treatment. The number of shoots per growing explant by 85%. The treatment of Vacint & Went (VW) and Nagata & Takebe (NT) media did not have enough effect on callus induction in the form of growth and development of callus planted in-vitro. So that the morphagenics of sorghum plants are good in the growth of shoots on Murashige & Skoog (MS) media.